Reduced maximal aerobic capacity after COVID-19 in young adult recruits, Switzerland, May 2020 - Crameri, G. A. G.; Bielecki, M.; Züst, R.; Buehrer, T. W.; Stanga, Z.; Deuel, J. W. (Eurosurveillance, 2020)
In March 2020, we observed an outbreak of COVID-19 among a relatively homogenous group of 199 young (median age 21 years; 87% men) Swiss recruits. By comparing physical endurance before and in median 45 days after the outbreak, we found a significant decrease in predicted maximal aerobic capacity in COVID-19 convalescent but not in asymptomatically infected and SARS-CoV-2 naive recruits. This finding might be indicative of lung injury after apparently mild COVID-19 in young adults.